Understanding Best Practices in Public Health Services and Leadership in Indonesia - Budi Sulistiyo Nugroho; Irma Rachmawati Maruf; B.M.A.S. Anaconda Bangkara; Imam Jayanto; Kholis Ernawati (Science Midwifery, 2022)
The issue of Leadership and public health services is a significant concern for governments, the wider community, and world health institutions. This study discusses several best practices in public health services based on the principle of health leadership in carrying out health service tasks, especially the government providing health services to the community as mandated by the constitution. This study uses secondary data such as academic publications, books, articles, and other literature relevant to public health service issues and leadership policies. We obtained data through electronic searches in several journals through the Google Scholar application. We then reviewed several stages of analysis, such as coding the data, analyzing sensitive data, evaluating the data, interpreting the data, and concluding the results. Study with a phenomenological approach to obtain valid and highly valid findings. We believe that these results answer the problem of this study. We found, among other things, that health services and Leadership must depart from the first three principles, namely the nature of Leadership with knowledge or understanding of public health conditions, Leadership that has strategic connectivity that combines knowledge, expertise, and experience to support the success of public health services in Indonesia, especially in the era of the pandemic crisis, entering a new normal. The results of this study are expected to be essential inputs for future research and contribute to strengthening decision-making in the field.